Horse shoe anorectal abscess in pregnancy: fetus vs abscess - Bandegudda, Santhoshkumar; Gopal, Ajesh; Mohandas, Anu (International Surgery Journal, 2022)
Anorectal diseases such as hemorrhoids and anal fissures are the common entities encountered during pregnancy. However anorectal abscess is uncommon condition warrants emergency surgery. There is a significant risk of adverse outcomes, premature birth, and fetal loss due to surgery. A strategic approach considering risk and benefit is required in managing such conditions. We report one such case of horseshoe abscess in a 19 years old pregnant lady.